A Single Conserved Amino Acid Residue as a Critical Context-Specific Determinant of the Differential Ability of Mdm2 and MdmX RING Domains to Dimerize - Kosztyu, Pavlína; Slaninová, Iva; Valčíková, Barbora; Verlande, Amandine; Müller, Petr; Paleček, Jan J.; Uldrijan, Stjepan (Frontiers in Physiology, 2019)
Mdm2 and MdmX are related proteins serving in the form of the Mdm2 homodimer or Mdm2/MdmX heterodimer as an E3 ubiquitin ligase for the tumor suppressor p53. The dimerization is required for the E3 activity and is mediated by the conserved RING domains present in both proteins, but only the RING domain of Mdm2 can form homodimers efficiently. We performed a systematic mutational analysis of human Mdm2, exchanging parts of the RING with the corresponding MdmX sequence, to identify the molecular determinants of this difference. Mdm2 can also promote MdmX degradation, and we identified several mutations blocking it. They were located mainly at the Mdm2/E2 interface and did not disrupt the MdmX-Mdm2 interaction. Surprisingly, some mutations of the Mdm2/E2 interface inhibited MdmX degradation, which is mediated by the Mdm2/MdmX heterodimer, but did not affect p53 degradation, mediated by the Mdm2 homodimer. Only one mutant, replacing a conserved cysteine 449 with asparagine (C449N), disrupted the ability of Mdm2 to dimerize with MdmX. When we introduced the cysteine residue into the corresponding site in MdmX, the RING domain became capable of forming dimers with other MdmX molecules in vivo, suggesting that one conserved amino acid residue in the RINGs of Mdm2 and MdmX could serve as the determinant of the differential ability of these domains to form dimers and their E3 activity. In immunoprecipitations, however, the homodimerization of MdmX could be observed only when the asparagine residue was replaced with cysteine in both RINGs. This result suggested that heterocomplexes consisting of one mutated MdmX RING with cysteine and one wild-type MdmX RING with asparagine might be less stable, despite being readily detectable in the cell-based assay. Moreover, Mdm2 C449N blocked Mdm2-MdmX heterodimerization but did not disrupt the ability of Mdm2 homodimer to promote p53 degradation, suggesting that the effect of the conserved cysteine and asparagine residues on dimerization was context-specific. Collectively, our results indicate that the effects of individual exchanges of conserved residues between Mdm2 and MdmX RING domains might be context-specific, supporting the hypothesis that Mdm2 RING homodimers and Mdm2-MdmX heterodimers may not be entirely structurally equivalent, despite their apparent similarity.